2017
DOI: 10.1111/1471-0528.14543
|View full text |Cite
|
Sign up to set email alerts
|

Serous tubal intraepithelial carcinomas associated with high‐grade serous ovarian carcinomas: a systematic review

Abstract: A systematic review of the incidence of STICs in HGSOCs identifies significant methodological inconsistencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 37 publications
0
51
0
Order By: Relevance
“…Larger studies will be required to test these hypotheses. Epithelial cell dynamics in the fallopian tube have not been extensively studied, but in the last two decades, interest in this organ has been piqued by strong evidence to support a fallopian tube origin for the majority of high-grade serous 'ovarian' carcinomas (Callahan et al, 2007;Chen et al, 2017;Lee et al, 2007;Medeiros et al, 2006;Meserve et al, 2017). The pseudostratified epithelium of the fallopian tube consists of two major cellular populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Larger studies will be required to test these hypotheses. Epithelial cell dynamics in the fallopian tube have not been extensively studied, but in the last two decades, interest in this organ has been piqued by strong evidence to support a fallopian tube origin for the majority of high-grade serous 'ovarian' carcinomas (Callahan et al, 2007;Chen et al, 2017;Lee et al, 2007;Medeiros et al, 2006;Meserve et al, 2017). The pseudostratified epithelium of the fallopian tube consists of two major cellular populations.…”
Section: Discussionmentioning
confidence: 99%
“…The pseudostratified epithelium of the fallopian tube consists of two major cellular populations. A secretory population that expresses the PAX8 transcription factor is thought to be the predominant cell-of-origin for HGSC (Callahan et al, 2007;Chen et al, 2017;Ducie et al, 2017;Lawrenson et al, 2019;Lee et al, 2007;Medeiros et al, 2006;Meserve et al, 2017). Fallopian secretory epithelia are more proliferative in vitro and in vivo and less competent at repairing DNA damage compared to the FOXJ1-positive ciliated population (Levanon et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The epithelium of STIC showed strong p53 positivity and harbors clonal TP53 mutations (12). It has been suggested that STIC is found in 11-68% of HGSC patients (12,20,21) as well as up to 60% of sporadic cancer cases and in 0.6-10% of the carriers of patients with hereditary cancer (22). Conversely, the frequency of fallopian tube precursors in benign gynecologic diseases was approximately 20% of SCOUT, 10% of p53 signature and <4% of STIC cases (1,2).…”
Section: Histopathology Of Precursor Lesionsmentioning
confidence: 99%
“…Based on multiple studies, the frequency of an intramucosal carcinoma in the fallopian tube of the patient with a symptomatic HGSC ranged from as low as 10% to as high as 60%. 18 Either estimate left a large percentage of HGSC in which a clear-cut early malignancy in the fallopian tube could not be identified. Proponents of other potential sources pointed to the ovarian surface epithelium or the secondary Mullerian system.…”
Section: Unanswered Questionsmentioning
confidence: 99%